Information System of Railway Undertakings Train Track Requirements - Greiner, Karel (Promet - Traffic&Transportation, 2012)
The paper describes the facilities of a new application serving for entering railway undertakings requirements related to train tracks in the conditions of the Czech Republic. The application is a part of a new information system of the train timetables configuration. The train editor represents a distributed application consisting of a database server, application server and a client program. It contains most of the data of trains available in the programming schedule. In addition to features for working with trains, it provides a variety of analytical tools and printing of tools for railway workers and passengers. In order to coordinate compiling of the timetable by the infrastructure manager, a train-making procedure was designed based on the stages of the train.KEY WORDS: timetable, train, information system, distributed application